THE ECOLOGICAL CONSEQUENCES OF HABITAT AND MICROHABITAT USE IN LIZARDS:: A REVIEW - Smith, Geoffrey R.; Ballinger, Royce E. (Contemporary Herpetology, 2001)
We review the ecological consequences of habitat and microhabitat use in lizards. Different habitats have different biotic and abiotic properties and thus are likely to have different consequences for the lizards that occur in them. Individual performance and life histories are influenced by habitat use, particularly when habitats differ in thermal characteristics that may influence physiological processes or constrain activity. We know relatively little about how the effects of habitat use on individual performance translate into population dynamics. We do know that the ability of lizards to use particular habitats can influence the persistence of populations in the face of habitat changes. Community-level processes (e.g., competition) and community structure (e.g., diversity) can be influenced by habitat use in lizards, often by habitat use facilitating co-existence of two or more potentially competing species. We know relatively little about how other community processes, such as predation and parasitism, are influenced by habitat use.